Важнейшие местонахождения гиппарионовой фауны на территории УССР - Короткевич, Е.Л. (Вестник зоологии, 1976)
According to the latest data, there are about 20 sites of the Hipparion fauna in the territory of the Ukrainian SSR, 14 of them are studied by the author. The article contains enumeration of the main sites, indication of their age, a brief taphonomic characteristic and specified list of the fauna. As a result of the carried investigations the different age is determined for coastal-continental deposits of the Northern Black Sea area, the possibility of their separation on the basis of species composition of the terrestrial vertebrates fauna is stated and a subsequent change of the fauna composition is determined not only within the limits of the stage, but also within individual substages of Late Neogene.